Algal Flora of Gunde Lake, Lekhnath Municipality, Kaski District, Gandaki Province, Nepal - Dhakal, Sajita; Chalise, Pratikshya; Thapa, Sangita (Journal of Plant Resources, 2024)
Algae play a crucial role in maintaining life on earth, are beneficial to aquatic ecosystems and serve as excellent indicators of water pollution. The current study was carried out to identify algal species from Gunde Lake, Lekhnath, Central Nepal. Microscopic images were taken and studied to identify algal species. A total of 50 species were recorded that belong to 13 orders, 16 families and 29 genera including new records of three taxa for Nepal viz. Cosmarium capense var. nyassae, Staurastrum forficulatum and Staurastrum polytrichum. Among identified taxa, Closterium was the most common genus with 10 species accounting for 20% of the total number of species. The second most common genus was Staurastrum with six species, contributing 12% of the total number of species. Hence, the current study reveals that Gunde Lake is rich in algal flora.